THE FARMER LIVELIHOOD ASSET ON BANANA FARMING IN EAST JAVA - Dwi Retno Andriani; Budi Setiawan; Djoko Koestiono; Abdul Wahib M (Agricultural Socio-Economics Journal, 2020)
This Research aims to find out and analyze the performance of banana farmers in East Java, from the aspect of livelihood assets which include human assets, natural, financial, physical, and social.  This study using the Sustainable Livelihood Approach method. Results show that the analysis of sustainable livelihood approach showed that the ability of banana farmers to access resources was influenced by 5 assets : human assets 52.53%, natural assets 44.70%, financial assets 39.53%, physical assets 49 , 40%, and social assets of 60.27%.  Banana farmers have a high ability in using social resources and  weak in using  financial resources, because in banana agribusiness funding, majority of farmers use their own limited capital. From  three districts that have the highest access to resources is Malang district, with an average ability to access resources is 51.8%.